Integrating Islamic Values and Industrial Technology in Accounting Education: A Thematic Comparison of Student Competencies at Umbandung and Unikl - Nazihah Amatullah; Erfan Erfiansyah; Nur Ezzatte Azzahrah Binti Kuzaidi (Greenation Research & Yayasan Global Resarch National, 2025)
Globalization and digital transformation have reshaped the competency demands of the accounting profession. This study aims to explore competency gaps among accounting students from two institutions with different curricular orientations: Universitas Muhammadiyah Bandung (UMBandung), which emphasizes Islamic values, and Universiti Kuala Lumpur (UniKL), which focuses on industrial technology. A qualitative case study approach was employed, involving in-depth interviews with 15 final-year students, analyzed thematically. The findings reveal significant thematic contrasts. UMBandung students demonstrated strong ethical internalization and sustainability awareness grounded in values, yet showed limited proficiency in accounting software, professional presentation, and cross-cultural exposure. In contrast, UniKL students exhibited strong mastery of industrial technology tools (e.g., Structured Query Language (SQL)) and professional communication skills, but their understanding of ethics remained procedural and lacked reflective depth. Both institutions also lacked sufficient coverage of international taxation and global accounting practices. The study highlights a pattern wherein value-based curricula tend to strengthen personal integrity, while industry-based curricula emphasize technical job readiness. The key contribution of this research lies in offering empirical insights for developing a more holistic and contextually relevant accounting curriculum in Southeast Asia one that integrates local values with global industry needs to produce ethical, adaptive, and professionally competent accountants.